THE USE OF ABBREVIATED DICTION IN ARGOT LANGUAGE ON SOCIAL MEDIA (EXPLORATIVE STUDY ON THE GAY AND LESBIAN COMMUNITIES) - JOKO SANTOSA; RANI SETIAWATY; AGUS BUDI WAHYUDI; ATIQA SABARDILA; EKO PURNOMO; ANGGARA TIYO (Bahtera Indonesia, 2022)
Argot language is a secret language and it is only a particular group knows its meaning. One of argot language dictions that are often used by the communities gay and lesbian is abbreviation or abridgment. This study aims to describe: (1) the use of diction in argot language used by the gay and lesbian communities and (2) the function of argot language used by the gay and lesbian communities. The study approach is descriptive qualitative. Data are abbreviated diction containing argot language of the gay and lesbian communities. Data sources are utterances of the gay and lesbian communities on social media, including Twitter, Telegram groups, and WhatsApp groups. Data collection technique uses documentation and data analysis technique uses content analysis. The results indicate that the communication done by gay and lesbian communities on social media contains argot language using abbreviated diction which includes (a) abbreviations, (b) behadings, (c) acronyms, and (d) letter symbols. The use of abbreviated diction aims to speed up and simplify the communication process. As for the language functions that arise are emotive, referential, fatigue, and connotative functions.